Studies of Marine Chemical Pollution at Turkish Straits and Sea of Marmara - INCAZ, SERAP; BILEN ALKAN, GULER (Asian Journal of Chemistry, 2010)
In this paper, the effecs of the marine chemical pollution are discussed on the Turkish Straits and Sea of Marmara. It is also aimed to show the environmental impacts of intense maritime traffic depending on numerical values in the same region.